2015
DOI: 10.1007/s00787-015-0733-1
|View full text |Cite
|
Sign up to set email alerts
|

Emotional face recognition in adolescent suicide attempters and adolescents engaging in non-suicidal self-injury

Abstract: Little is known about the bio-behavioral mechanisms underlying and differentiating suicide attempts from non-suicidal self-injury (NSSI) in adolescents. Adolescents who attempt suicide or engage in NSSI often report significant interpersonal and social difficulties. Emotional face recognition ability is a fundamental skill required for successful social interactions, and deficits in this ability may provide insight into the unique brain-behavior interactions underlying suicide attempts versus NSSI in adolescen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
1
12

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 90 publications
1
28
1
12
Order By: Relevance
“…This trend was also observed at the lowest intensity of fear at 50%, which came out slightly above the conservatively adjusted pvalue to accommodate for the multiple comparisons. These results appear in line with the observations made by Seymour et al, [52] who found that inpatient adolescents engaged in NSSI made more emotional face recognition errors for child fearful faces compared to typically developing controls. Among other reasons, theoretical models of NSSI postulate that engaging in NSSI may be used by individuals as a means for social communication to gain attention or influence other's behavior [63][64].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This trend was also observed at the lowest intensity of fear at 50%, which came out slightly above the conservatively adjusted pvalue to accommodate for the multiple comparisons. These results appear in line with the observations made by Seymour et al, [52] who found that inpatient adolescents engaged in NSSI made more emotional face recognition errors for child fearful faces compared to typically developing controls. Among other reasons, theoretical models of NSSI postulate that engaging in NSSI may be used by individuals as a means for social communication to gain attention or influence other's behavior [63][64].…”
Section: Discussionsupporting
confidence: 92%
“…However, this study also used sad and neutral mood induction to evoke specific mood states before presenting the stimuli, which was not the case for the current research or the Ziebell et al, [30] study. Seymour et al [52], who also used static images for their experiment, found that adolescents engaging in NSSI made more errors on child fearful and adult sad face recognition compared to the typically developing controls.…”
Section: Discussionmentioning
confidence: 99%
“…An increased tendency to interpret neutral facial expressions as sad has been reported in adult patients with “affective temperaments” in one study [ 137 ], and more errors in the recognition of facial expressions of “disgust” in another study [ 138 ]. Youth with a history of engaging in non-suicidal self-injury and those with past suicide attempts were found to make more errors in sad face recognition [ 139 ], and children with suicidal ideation were found to misclassify angry emotions as sad [ 140 ]. The percent of correct identifications of the three facial expressions were compared between participants with a history of suicidal thoughts and those without in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Given that biased self-schemas and self-referential processing biases are prevalent among depressed and suicidal youth, atypical processing of self-faces may be characteristic of youth at risk for suicide. Prior research has established that attention, perception, and identification biases for affective facial stimuli are robust among youth with emotional disorders and symptoms, including suicidality (Hankin, et al, 2010; Joormann, Gilbert, & Gotlib, 2010; Seymour et al, 2015), although these studies have not focused on self-faces specifically. Emotional facial stimuli are frequently used in these information processing studies, because processing of facial emotional expressions are rapid and automatic (Vuilleumier & Schwartz, 2001), and are believed to function external to awareness (Gotlib & Neubauer, 2000).…”
Section: Relevance Of Self-face Processing For Understanding Suicide mentioning
confidence: 99%